(untitled) (Research, Society and Development, 2021)
Locker is a fungicide used in different crops for biological control, affecting both insect pests and pollinators, such as bees. This study aimed to evaluate toxicity and establish the lethal concentration (LC50) of the fungicide Locker in stingless bees Scaptotrigona bipunctata, investigating changes in brain cells chromatin structure and in midgut morphology. This agrochemical is a combined fungicide that contains three active ingredients: benzimidazole, triazole and strobilurin. Adult forage bees were orally exposed to the following concentrations: 1.7 mg a.i./L; 2.55 mg a.i./L; 3.4 mg a.i./L and 4.25 mg a.i./L of fungicide, and submitted to histochemical and morphological analysis 24, 48 and 72 hours after ingestion. The analysis of S. bipunctata brain cells showed changes in chromatin condensation in all treatments. There were also several morphological changes in the midgut at all concentrations and exposure times. Thus, the fungicide Locker significantly affected bee survival, inducing changes in their internal morphology, which can lead to alterations in their activities, directly interfering in their foraging behavior and survival.